Heat-Killed Lacticaseibacillus paracasei GMNL-653 Exerts Antiosteoporotic Effects by Restoring the Gut Microbiota Dysbiosis in Ovariectomized Mice - Jhong, Jhih-Hua; Tsai, Wan-Hua; Yang, Li-Chan; Chou, Chia-Hsuan; Lee, Tzong-Yi; Yeh, Yao-Tsung; Huang, Cheng-Hsieh; Luo, Yueh-Hsia (Frontiers in Nutrition, 2022)
Osteoporosis is a metabolic inflammatory disease, an imbalance occurs between bone resorption and formation, leading to bone loss. Anti-inflammatory diet is considered having the potential to ameliorate osteoporosis. Heat-killed probiotics exhibit health benefits in relation to their immunomodulatory effects, but the detail mechanism involved in gut microbiota balance, host metabolism, immunity, and bone homeostasis remains unclear. In this study, we evaluated the antiosteoporotic effects of heat-killed Lacticaseibacillus paracasei GMNL-653 in vitro and in ovariectomized (OVX) mice. Furthermore, whole-genome sequencing and comparative genomics analysis demonstrated potentially genes involved in antiosteoporotic activity. The GMNL-653 exerts anti-inflammatory activity which restored gut microbiota dysbiosis and maintained intestinal barrier integrity in the OVX mice. The levels of IL-17 and LPS in the sera decreased following GMNL-653 treatment compared with those of the vehicle control; mRNA levels of RANKL were reduced and TGF- and IL-10 enhanced in OVX-tibia tissue after treatment. The levels of IL-17 were significantly associated with gut microbiota dysbiosis. Gut microbial metagenomes were further analyzed by PICRUSt functional prediction, which reveal that GMNL-653 intervention influence in several host metabolic pathways. The analysis of whole-genome sequencing accompanied by comparative genomics on three L. paracasei strains revealed a set of GMNL-653 genes that are potentially involved in antiosteoporotic activity. Our findings validated antiosteoporotic activity of heat-killed GMNL-653 using in vitro and in vivo models, to whole-genome sequencing and identifying genes potentially involved in this gut microbiota–bone axis.